Violence at work in emergency care units: nurses' experiences - Camila de Souza Oliveira; Júlia Trevisan Martins; Maria José Quina Galdino; Renata Ribeiro Perfeito (Universidade de São Paulo, 2020)
Objectives: to understand the perception of nurses in emergency care units about the violence experienced at work. Method: qualitative study conducted through 21 individual interviews between November and December 2018 in two emergency care units in a city in Paraná. Symbolic Interactionism was adopted as the theoretical framework and the Thematic Content Analysis technique was used to evaluate the data. Results: from the thematic category experiencing psychological violence in the nurses' daily work, it was evidenced that it was related to threats against their lives, cursing, humiliation, embarrassment, attempt to defame them, as well as pressure from subordinates. In the category experiencing physical violence in the nurses' daily work, it was found that it was imposed through pushing, pulling hair, throwing objects, the presence of firearms and knives and, even, witnessing murder. Conclusion: nurses suffered acts of violence by external and internal people, from the emergency care units themselves. Managers, nurses and society need to look reflexively and critically at the violence that happens and implement actions to avoid them, thus providing a safe working environment for all involved and educate society in order to make the reduction of violence a priority in public policies.